Genomic-Based Restriction Enzyme Selection for Specific Detection of Piscirickettsia salmonis by 16S rDNA PCR-RFLP - Mandakovic, Dinka; Glasner, Benjamín; Maldonado, Jonathan; Aravena, Pamela; González, Mauricio; Cambiazo, Verónica; Pulgar, Rodrigo (Frontiers in Microbiology, 2016)
The gram negative facultative bacterium P. salmonis is the etiological agent of Salmonid Rickettsial Septicaemia (SRS), a severe disease that causes important economic losses in the global salmon farmer industry. Despite efforts to control this disease, the high frequency of new epizootic events indicate that the vaccine and antibiotics treatments have limited effectiveness, therefore the preventive and diagnostic approaches must be improved. A comparison of several methodologies for SRS diagnostic indicate differences in their specificity and its capacity to detect other bacteria coexisting with P. salmonis in culture media (contamination) and fish samples (coinfection), aspects relevant for research, vaccine development and clinical diagnostic. By computer-simulation analyses, we identified a group of restriction enzymes that generate unique P. salmonis 16S rDNA band patterns, distinguishable from all other bacteria. From this information, we designed and developed a PCR-RFLP (Polymerase Chain Reaction - Restriction Fragment Length Polymorphism) assay, which was validated using 16S rDNA universal primers and restriction enzyme PmaCI for the amplification and digestion, respectively. Experimental validation was performed by comparing the restriction pattern of P. salmonis with the restriction patterns generated by bacteria that cohabit with P. salmonis (fish bacterial isolates and culture media contaminants). Our results indicate that the restriction enzyme selection pipeline was suitable to design a more specific, sensible, faster and cheaper assay than the currently used P. salmonis detection methodologies.